Studies on the synthesis and properties of a diazadiphosphapentalene - Cui, Jing Jing (2016)
The first four chapters of this thesis focus on the synthesis and reactivity investigation of a diazadiphospha-pentalene derivative. In chapter 1, phosphines are shown to be less powerful than NHCs in the content of low valent main group elements stabilization and small molecules activation. However with proper modifications of the substituents, the reactivity diversity of phosphines could be expanded. Inspired by some successful examples, we designed a diazadiphosphapentalene. Chapter 2 describes the synthesis and full characterization of the designed diazadiphosphapentalene 7. The solid-state molecular structure confirms a folded geometry with no significant delocalization of -electrons. The two phosphorus atoms at the bridgehead appear at very different position in the 31 P NMR spectrum implying a different electron environment of these two phosphorus centers. Chapter 3 shows the activation of ammonia and ammonia borane by 7. The mechanistic studies suggest ammonia activation proceeds via a σ-bond metathesis, and it is inferred that ammonia borane is activated in a similar way. Chapter 4 introduces the reactivity of the 7 towards various substrates such as electrophiles and Lewis acids. Only one of the two phosphorus centers exhibits nucleophilic property. The isomerization of 7 is also discussed. In the fifth chapter, a cyclic (alkyl)(amino)phosphorous chloride 22 was designed for the synthesis of a Lewis base free oxophosphonium ion. Compound 22 undergoes chloride abstraction and oxidation to afford amine-stabilized oxophosphonium ion 24. The thermal decomposition of 24 gives some crystals of the C−H activation product 25 which suggests the generation of Lewis base free oxophosphonium ions.